5.3k views
5 votes
How do i solve this equation​

How do i solve this equation​-example-1

1 Answer

3 votes

Answer:

x = -2 ±sqrt(7)

Explanation:

x^2 +4x =3

We will complete the square

Take the coefficient of the x term, divide by 2 and then square it

4, then divide by 2

4/2

Then square it

2^2 =4

Add 4 to each side

x^2 +4x +4 = 3+4

The left side is equal to (x+ the coefficent /2 )^2

(x+2)^2 = 7

Take the square root of each side

sqrt((x+2)^2) = ±sqrt(7)

x+2 = ±sqrt(7)

Subtract 2 from each side

x+2-2 = -2±sqrt(7)

x = -2 ±sqrt(7)

User Jonathan Guerrera
by
6.0k points